Small modifier, big decision: switching to SUMO mode adds weight to cancer stemness in mammary tumors - Yevdokimova, Veronika; Benoit, Yannick D. (Molecular oncology, 2025)
Protein SUMOylation is crucial for maintaining the hallmarks of cancer stem cells, including self‐renewal and active pluripotency gene networks. While inhibiting key steps of the SUMOylation cascade has been shown to suppress tumorigenesis, the specific mechanisms of SUMO dependency in cancer have not been comprehensively characterized. Li et al. applied genetically engineered models of mammary gland tumorigenesis to demonstrate that SUMOylation of the transcription factor Etv1 is essential for maintaining cancer stem cell functions. Moreover, SUMO conjugation of Etv1 acts as a switch between stem and nonstem cancer cell states. Here, we discuss the implications of these findings regarding the role of SUMOylation‐dependent mechanisms in the hierarchical organization of malignant cells and intratumor heterogeneity and highlight potential therapeutic approaches harnessing the SUMOylation cascade. Inhibition of protein SUMOylation has been shown to block tumorigenesis; however, the specific mechanisms by which SUMOylation controls the tumor‐initiating capacities remain elusive. Li et al. describe the role of Etv1 SUMOylation in cancer stem cells using mouse models of mammary gland tumorigenesis. Here, we discuss the implications of these findings and highlight potential anticancer therapeutic approaches targeting this cascade.